2001
DOI: 10.1080/01690960143000083
|View full text |Cite
|
Sign up to set email alerts
|

Sequence detection in pseudowords in French: Where is the syllable effect?

Abstract: In two experiments, French speakers detected cv or cvc sequences at the beginning of disyllabic pseudowords varying in syllable structure and pivotal consonant. Overall, both studies failed to replicate the crossover interaction that has been previously observed in French by Mehler, Dommergues, Frauenfelder and Seguṍ (1981). In both experiments, latencies were shorter to cv than to cvc targets and this effect of target length was generally smaller for cvc . cv than for cv . cv carriers. However, a clear crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
40
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 17 publications
7
40
0
1
Order By: Relevance
“…Indeed, Dupoux et al (1999) and Dehaene-Lambertz et al (2000), while reporting data on the mora, couch their explanation in terms of a proposal originally formulated for the syllable (Mehler, Dupoux & Segui, 1990). However, note that recent evidence on the role of the syllable in processing spoken French Content, Meunier et al, 2001) is also entirely consistent with our present universalist perspective: rhythmic boundaries are relevant for segmentation, but rhythmic units do not intervene as independent structural units. Content and colleagues report several converging lines of experimental evidence from French, from phoneme monitoring, fragment monitoring, word spotting, and explicit segmentation judgements and conclude that syllables do not constitute indivisible units which participate in the perceptual processing of spoken French.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, Dupoux et al (1999) and Dehaene-Lambertz et al (2000), while reporting data on the mora, couch their explanation in terms of a proposal originally formulated for the syllable (Mehler, Dupoux & Segui, 1990). However, note that recent evidence on the role of the syllable in processing spoken French Content, Meunier et al, 2001) is also entirely consistent with our present universalist perspective: rhythmic boundaries are relevant for segmentation, but rhythmic units do not intervene as independent structural units. Content and colleagues report several converging lines of experimental evidence from French, from phoneme monitoring, fragment monitoring, word spotting, and explicit segmentation judgements and conclude that syllables do not constitute indivisible units which participate in the perceptual processing of spoken French.…”
Section: Discussionsupporting
confidence: 68%
“…Specifically, a single-phoneme context which was in its own right a mora did not reduce activation of an adjacent word as drastically as did a single-phoneme context which was nonmoraic. It has also recently been claimed by see also Content, Meunier, Kearns, & Frauenfelder, 2001) that the role of the syllable in the recognition of spoken French accords with Norris et al's proposal; the syllable does not constitute an intermediate level of representation on which lexical access is based, but syllable boundaries are nevertheless relevant to lexical activation in that they constitute likely word boundaries.…”
supporting
confidence: 53%
“…However, the effect was not fully replicated in follow-up studies (e.g., Cutler, Mehler, Norris, & Segui, 1986;Tabossi, Collina, Mazzetti, & Zoppello, 2000). In particular, Content, Meunier, Kearns, and Frauenfelder (2001) showed that syllable congruency effects in French emerged only under restrictive conditions, namely, for target words including a liquid pivotal consonant (e.g., bal.con).…”
mentioning
confidence: 96%
“…That is, listeners were faster to detect target sequences when they matched the syllabification of the target-bearing words. Although the generalizability of this original finding has recently been called into question (Content et al, 2001b), it remains clear that French listeners use syllabic structure in speech segmentation (Content et al, 2001a, b;Dumay et al, 2002).One might therefore predict that French listeners will have difficulty recognizing words which are misaligned with syllable boundaries, like oignon in dernier oignon. But French listeners generally do not appear to have problems with word recognition in liaison environments.…”
mentioning
confidence: 99%